Hydrophobic ionic liquid modified thermoresponsive molecularly imprinted monolith for the selective recognition and separation of tanshinones. Issue 17 (23rd July 2018) - Tang, Weiyang; Row, Kyung Ho
Abstract: A hydrophobic ionic liquid modified thermoresponsive molecularly imprinted monolith was synthesized using N ‐isopropylacrylamide as a thermoresponsive monomer and a long‐chain hydrophobic ionic liquid as an auxiliary modification monomer. The ionic‐liquid‐modified thermoresponsive molecularly imprinted polymer was characterized by scanning electron microscopy and Fourier transform infrared spectroscopy. When the column temperature was 50°C, the synthesized monolithic column was successfully applied to the selective separation of homologue tanshinones within 7 min and eluted only by water (mobile phase) (theoretical plates more than 1.00 × 10 5 per meter). The negative Gibbs free energy (≤–2.37) values showed that the transfer of the tanshinones from the mobile phase to the stationary phase on this monolithic column was a thermodynamically spontaneous process. Good linearity of the five tanshinones by thermoresponsive monolith was obtained in the range of 0.100–25.0 μg/mL. The limit of detection (S/N = 3) and limit of quantitation (S/N = 10) were less than 0.0390 and 0.0630 μg/mL, respectively, with a relative standard deviation of <4.8%. In this proposed thermoresponsive chromatography method, the separation of homologue analytes can be achieved by changing the column temperature, and the use of water as the mobile phase would decrease the economic cost and organic pollution.